2007
DOI: 10.1097/nmd.0b013e31815c1a1d
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness in Schizophrenia: The Impact of Symptoms and Beliefs About Illness

Abstract: Risk factors for the development of hopelessness in schizophrenia remain poorly understood. This study investigated how psychiatric symptom levels and beliefs about illness might be linked to hopelessness in 100 patients with DSM-IV schizophrenia. Participants were assessed on the Beck Hopelessness Scale (BHS), the Calgary Depression Scale for Schizophrenia (CDSS), the Personal Beliefs about Illness Questionnaire (PBIQ), the Brief Psychiatric Rating Scale (BPRS), and the Scale for the Assessment of Negative Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 70 publications
1
32
0
2
Order By: Relevance
“…The correlation between self-reported hopelessness and negative symptoms supports earlier work in individuals with chronic schizophrenia (Kao et al, 2012;Lysaker et al, 2008;R. G. White et al, 2007) as well as those in their first episode of psychotic illness (Aguilar et al, 1997).…”
Section: Symptoms In Individuals With First Episode Psychosissupporting
confidence: 73%
See 2 more Smart Citations
“…The correlation between self-reported hopelessness and negative symptoms supports earlier work in individuals with chronic schizophrenia (Kao et al, 2012;Lysaker et al, 2008;R. G. White et al, 2007) as well as those in their first episode of psychotic illness (Aguilar et al, 1997).…”
Section: Symptoms In Individuals With First Episode Psychosissupporting
confidence: 73%
“…Participants in the other studies described had mean illness durations of 13 (R. G. White et al, 2007), 16 (Kao et al, 2012) and 22 (Lysaker et al, 2004;Lysaker et al, 2008) years (the latter figure is approximate, and is based on the figures reported for age at test minus age at first admission as specific illness duration was not reported).…”
Section: Future-directed Thinking and Negative Symptoms Of Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…The experience of psychosis has been shown to be associated with increased levels of depression (Rooke and Birchwood, 1998;Birchwood et al, 2000), hopelessness (White et al, 2007), social anxiety (Cosoff & Hafner, 1998;Gumley et al, 2003) and traumatic reactions sufficient to qualify for PTSD (Shaw et al, 2002;White & Gumley, 2009). Randomised clinical trials have found that Cognitive Behaviour Therapy for psychosis (CBTp) is efficacious for treating residual distressing positive and negative symptoms (Wykes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is a serious mental illness that is challenging to the primary caregiver [1,2]. Therefore, antipsychotic drugs have become an important part of the treatment for and symptom control of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%